An experimental evaluation of the thermal interface resistance between cold sprayed copper/ laser-textured alumina bi-layered composites. (1st June 2022) - Tregenza, Owen; Saha, Manabendra; Hutasoit, Novana; Hulston, Chris; Palanisamy, Suresh
Highlights: Cu - Al2 O3 bi-layered composites are manufactured using cold spray copper deposition. Al2 O3 substrates are laser-textured to create different ordered surface topographies. Thermal interface resistance (TIR) at the Cu - Al2 O3 interface is measured using light-flash analysis. The lowest measured range was 1 . 5610 − 6 − 1 . 4910 − 9 m 2 K/W, for a temperature range of 20–500 ∘ C, and a corresponding adhesion strength of 16.79 MPa. The results suggest some correlation between Al2 O3 substrate surface topography and the TIR, and an inverse relationship with adhesion strength. Abstract: The removal of heat across composite structures comprising a metal-ceramic interface is a common engineering challenge. To maximise heat removal, it is essential that the thermal interface resistance is minimised. This paper describes an experimental study of the thermal interface resistance between copper-alumina bi-layered composites. Samples are prepared using a novel cold spray copper particle deposition process on alumina substrates. To facilitate particle adhesion and enhance heat transfer contact area, substrates were textured with an ordered crosshatch pattern, using a micro-machining ablation laser, at different powers. Thermal resistance measurements were made using the transient light-flash method for bi-layered materials, using a NETZSCH LFA 467 hyper-flash analyser . The results show that the developed process produces a copper-alumina interface with a very low thermal resistance. In addition, the results suggest some correlation between substrate surface topography and the resistance, and an inverse relationship with the interface adhesion shear strength. The lowest measured resistance range was 1.56 × 10 − 6 − 1.49 × 10 − 9 m 2 · K / W, for a temperature range of 20 − 500 ∘ C, and a corresponding adhesion strength of 16.79 MPa .